An Enzymatic–Colorimetric Assay for the Quantification of Bifidobacterium - Bibiloni, Rodrigo (2000)
An enzymatic-colorimetric assay for the quantification of Bifidobacterium was developed. The method, based upon the standard detection of fructose-6-phosphate phosphoketolase activity, was optimized with respect to bacterial cell pretreatment, time of incubation, and substrate concentration. The relationship between bacterial biomass and phosphoketolase activity was linear in a wide spectrum of bacterial densities. Higher sensitivity over the standard method was achieved by using 0.25% Triton X-100 in the reaction mixture to pretreat the bacterial cells. Because autoaggregation is a frequent feature among Bifidobacterium strains, this simple and reproducible method offers good advantage over viable plate count and turbidimetric techniques. The methodology can also be applied to the assessment of adherent Bifidobacterium strains to human epithelial cells.